The Use of Higher Order Thinking Questions in Reading Comprehension to Improve the Students’ Critical Thinking - Dzakiah Dzakiah (Universitas Muhammadiyah Sorong, 2020)
This research attempts to find out whether the use of higher order thinking questions in reading comprehension classroom activities is effective in teaching critical thinking. All participants were second-grade students of Ulul Albab Islamic senior high school in Makassar, Indonesia. This research was conducted through pre-experimental study design with one group as the sample consists of 20 students. The instruments were reading tests used in both pre-test and post-test. The research findings indicated that the use of higher order thinking questions in reading comprehension is can improve the students’ critical thinking. It was proved by the mean score of pretest was 4.45then improved to be 6.50 in post test. It is also proved with t-test value. The researcher found that the value of t-test (8.542) was greater than t-table (2.093) at the level of significances. It means that there is a significant difference between the result of the students’ pre-test and post-test. Therefore, hypothesis H0 was rejected and H1 was accepted. Thus the researcher concludes that using higher order thinking questions in reading comprehension is effective in fostering critical thinking of the second year students of MA Ulul Albab Makassar.